Difluoromethylornithine, a Decarboxylase 1 Inhibitor, Suppresses Hepatitis B Virus Replication by Reducing HBc Protein Levels - Mao, Binli; Wang, Zhuo; Pi, Sidie; Long, Quanxin; Chen, Ke; Cui, Jing; Huang, Ailong; Hu, Yuan (Frontiers in Cellular and Infection Microbiology, 2020)
Current treatments of hepatitis B virus (HBV) are limited to Interferon-alpha or the nucleos(t)ide analogs antiviral therapies, and it is crucial to develop and define new antiviral drugs to cure HBV. In this study, we explored the anti-HBV effect of difluoromethylornithine (DFMO), an irreversibly inhibitor of decarboxylase 1(ODC1) on HBV replication. Firstly, we found that polyamines contributed to HBV DNA replication via increasing levels of the HBV core protein (HBc) and capsids. In contrast, depletion of polyamines either by silencing the expression of ODC1 or DFMO treatment, resulted in decreasing viral DNA replication and levels of HBc protein and capsids. Furthermore, we found that DFMO decreased the stability of the HBc protein without affecting mRNA transcription and protein translation. Taken together, our findings demonstrate that DFMO inhibits HBV replication by reducing HBc stability and this may provide a new approach for HBV therapeutics.